Impacts of extension dissemination and technology adoption on farmers' efficiency and welfare in Ghana: Evidence from legume inoculant technology - Mohammed, Sadick; Abdulai, Awudu (Frontiers in Sustainable Food Systems, 2022)
Examining the welfare impact of agricultural development interventions that incorporate diffusion of improved production technologies to farmers within extension delivery programs can be very challenging, because of the difficulty in disentangling the individual impacts of the production technology and the extension delivery program. Using recent farm level survey data from extension dissemination program of legume inoculant technology of 600 farmers in Ghana, we employ a recent methodological approach to investigate, simultaneously, the impact of the inoculant technology adoption and the extension program participation on farmers’ productivity, efficiency and welfare. We decompose each of these impact measures into subcomponents whose causal paths can be traced to both the adoption of the production technology and the extension delivery program. We find that, in terms of yields and net revenue, direct contribution of improved technology adoption alone is 34% and 64%, respectively, and 35% and 66% indirectly due to improved farmer efficiency, leading to 36% and 74% improvement in farmers’ welfare, respectively. On the other hand, direct contribution of extension delivery program participation alone is 66% and 36%, respectively, with 66% and 34% indirectly due to improved farmer efficiency, resulting in 64% and 26% improvement in farmers’ welfare, respectively.